Heat Strain Analysis in PT. IKI (Persero) Makassar Shipbuilding Workers - Nadia Nadia; Nasruddin Syam; Rahman Rahman (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Heat strain is the body's physiological response to heat stress received by a person. This research is a type of quantitative research with a cross-sectional study approach. The sampling technique in this study was random sampling with a total sample of 80 respondents. They are collecting data using questionnaires and interviews. Methods of data analysis using univariate and bivariate analysis with Chi-square test at 95% confidence level (p=0.05). The results showed a significant relationship between drinking water consumption and the heat strain factor (p=0.001); there was no relationship between the length of work and the heat strain factor (p=0.455) for workers in the production division at PT. IKI (Persero) 2023. It can be concluded that there is a relationship between the variable consumption of drinking water and the heat strain factor, and there is no relationship between the length of work and the heat strain factor in workers in the production division of PT. IKI (Persero). Suggested: There is a need for special attention from the agency on the importance of controlling heat stress to reduce the risk of occupational diseases in production workers at PT. IKI (Persero).